Characterization of starch structures isolated from the grains of waxy, sweet, and hybrid sorghum (Sorghum bicolor L. Moench) - Kang, Xuemin; Zhu, Wentao; Xu, Tongcheng; Sui, Jie; Gao, Wei; Liu, Zhiquan; Jing, Haichun; Cui, Bo; Qiao, Xuguang; Abd El-Aty, A. M. (Frontiers in Nutrition, 2022)
In this study, starches were isolated from inbred (sweet, waxy) and hybrid (sweet, waxy) sorghum grains. Structural and property differences between sweet and waxy sorghum starches were evaluated and discussed. A lower intermediate fraction and amylose content were present in hybrid sweet starch than in inbred sweet starch, while the opposite trend occurred with waxy starch. Furthermore, there was a higher A chain (30.93 to 35.73% waxy, 13.73 to 31.81% sweet) and lower B2 + B3 chain (18.04 to 16.56% waxy, 24.07 to 17.43% sweet) of amylopectin in hybrid sorghum starch. XRD and FTIR measurements affirm the relative crystalline and ordered structures of both varieties as follows: inbred waxy > hybrid waxy > hybrid sweet > inbred sweet. SAXS and 13C CP/MAS NMR proved that the amylopectin content of waxy starch was positively correlated with lamellar ordering. In contrast, an opposite trend was observed in sweet sorghum starch due to its long B2 +B3 chain content. These findings could provide a basic theory for the accurate application of existing sorghum varieties precisely